Phylogenetical Relationships between Kejobong Goat and Other Goats Based on Mt-DNA D-loop Sequence Analysis - D. A. Lestari; E. Purbowati; S. Sutopo; E. Kurnianto (Faculty of Animal Science, Bogor Agricultural University, 2018)
The aim of this study was to investigate phylogenetical relationships between Kejobong goat and Kacang goat as well as Etawah Grade goat using genetic diversity, haplotype, and genetic distance analysis based on D-loop sequences. A total of 76 blood samples belonged to three local goats, namely Kacang goat (KC), Etawah Grade goat (EG), and Kejobong goat (KJ). The DNA genome was extracted based on the manufacturer’s standard protocol using gSYNC DNA Mini Kit (Geneaid Biotech Ltd.) for sequence analysis control region (D-loop) in mitochondrial DNA (mtDNA) using specific primer. The results revealed that there were a total of 36 nucleotide substitutions, those were 1 indel (insertion or deletion), 34 haplotypes with Pi = 0.00253±0.00029 and Hd = 0.925±0.018 in three local goats, while intra-breed in this study showed Pi value of EG, KC, and KJ were 0.00452±0.00077, 0.00214±0.00028 and 0.00143±0.00018, respectively and Hd value were 0.985±0.025, 0.926±0.032, and 0.855±0.044, respectively. Genetic distances between KJ and KC, KJ and EG, and between KC and EG were 0.0018; 0.0034, and 0.0036, respectively. The highest NHap was observed in KC (17), followed by EG (15) and KJ (11); and all three local goats were in the same cluster in phylogeny tree. In conclusion, genetically, Kejobong goat is a crossbred of Kacang goat and Etawah Grade goat and has closer genetic relationships to Kacang goat than to Etawah Grade goat.